2019
DOI: 10.14527/pegegog.2019.033
|View full text |Cite
|
Sign up to set email alerts
|

The effect of design based science education applications of science teacher candidates on their perceptions of engineering education and engineer

Abstract: The purpose of this study was to determine the effect of Design Based Science Education (DBSE) applications on the perceptions of science teacher candidates about engineering education and engineers. In the quantitative part of the study in which the mixed method was involved, a semi-experimental design with single group pre-test post-test was used while a case study design was adopted in the qualitative part of the study. The study group of the research consisted of 52 juniors who were receiving education at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…This finding indicates that the PSTs still considered engineering as an individualistic profession rather than a profession that requires teamwork and collaboration among people with various expertise. Existing studies on preservice and inservice teachers' views of engineers have reported similar findings that the participants emphasize more on individualistic and technical skills and characteristics rather than social characteristics while describing a good engineer (Ergün and Kıyıcı, 2019;Hammack and Ivey, 2017). During the STEM course that was designed and implemented in the present study, the PSTs were totally free in their groups to assign duties to group members.…”
Section: Views About Engineers and Engineeringsupporting
confidence: 64%
See 1 more Smart Citation
“…This finding indicates that the PSTs still considered engineering as an individualistic profession rather than a profession that requires teamwork and collaboration among people with various expertise. Existing studies on preservice and inservice teachers' views of engineers have reported similar findings that the participants emphasize more on individualistic and technical skills and characteristics rather than social characteristics while describing a good engineer (Ergün and Kıyıcı, 2019;Hammack and Ivey, 2017). During the STEM course that was designed and implemented in the present study, the PSTs were totally free in their groups to assign duties to group members.…”
Section: Views About Engineers and Engineeringsupporting
confidence: 64%
“…According to the findings, the number of PSTs' holding uninformed and partially informed views on the aspect of the nature of engineering were decreased and fully informed views were increased prominently. Ergün and Kıyıcı (2019) examined how PSTs' perceptions of engineering education and engineers changed after enrolling in a 14-week-long science education laboratory applications course, which was specifically designed to involve engineering design-based applications. In this pre-post design, mixed research study, PSTs' perceptions of engineering education and engineers were measured through Engineering Education Survey and Draw an Engineer Test.…”
Section: Psts' Views About Engineers and Engineeringmentioning
confidence: 99%
“…We can review from the aspect of individual capability. Internet network aspect and application device used to be considered so that online learning is carried out well [17]. Then what is this online learning solution for work from home program?…”
Section: Introductionmentioning
confidence: 99%
“…The methodological approach on teaching STEM has recently evolved in education from using traditional media to more advanced technological media [44,45]. Moreover, more and more studies are associated with other teaching methods considered innovative, such as online learning, gamification, learning communities, design-based science education or augmented reality [46][47][48][49][50][51]. This methodology brings to the educational field another active teaching method, which allows to develop the competences of the students towards the society [28].…”
Section: Introductionmentioning
confidence: 99%